Influência da glicerina na adsorção de tensoativos em arenitos e na recuperação de petróleo - Leite, Danilo Fernandes Queiroga (2017)
Over time, the production of oil in a reservoir tends to decrease, both by reducing the volume of oil in the reservoir and by the pressure drop, as well as by the change in the physicalchemical properties of the oil, which make it difficult to flow through the reservoir to the well, making its production more difficult and costly. Due of their physical properties, such as lower water/oil interfacial tension, surfactants have been used in enhanced oil recovery processes (EOR), where their adsorption to rock is undesirable and unavoidable, since the decrease of concentration of the surfactant can reduce the efficiency of the method. Glycerin has been incorporated in many industrial processes, such as the manufacture of cosmetics, paints and lubricants, because it has a high viscosity and is a very produced by-product. This work aims to evaluate the influence of glycerin on the adsorption of surfactants in sandstones (reservoir rock) to improve the oil recovery factors during EOR. Adsorption and oil recovery tests were carried out using solutions of the surfactant designed saponified coconut oil (SCOcom), with and without glycerin, and with KCl. The sandstone was used as adsorbent because it is the most common type of rock found in Brazilian reservoirs. The experimental procedures were: determination of the critical micelle concentration (CMC); bath adsorption test to evaluate the loss of surfactant in the rock; recovery test and adsorption in fixed bed; rheology of the solutions used in fixed bed EOR, Thermogravimetric Analysis (TGA) and X-ray Diffraction (XRD). SCOcom was effective in oil recovery, an improvement in the oil mobility was observed with the addition of glycerin, as it contributed to increase the viscosity of the solution, improving the efficiency of sweeping. The Thermogravimetric analysis showed that there was no significant mass loss of the components of the solution at temperatures near the oil wells (55 oC). The recovery factor obtained for the solution of surfactant SCOcom with glycerin was satisfactory, being 53% higher than without glycerin, and it can be indicated for use in EOR because it is a surfactant of vegetable origin, biodegradable, easy to obtain and low cost.